Editorial: The Remasculinization of Global Politics in the Contemporary Era - Dias Pabyantara Swandita Mahayasa (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2025)
Editorial: The Remasculinization of Global Politics in the Contemporary Era